Development of a 3D printable and highly stretchable ternary organic–inorganic nanocomposite hydrogel. Issue 22 (26th May 2021) - Hu, Chen; Haider, Malik Salman; Hahn, Lukas; Yang, Mengshi; Luxenhofer, Robert
Abstract : A novel 3D printable hybrid hydrogel is developed and characterized in detail in this study. After chemical curing of the 3D-printed constructs, the resulting hydrogel shows excellent mechanical strength with a tensile strain at break exceeding 550%. Abstract : Hydrogels that can be processed with additive manufacturing techniques and concomitantly possess favorable mechanical properties are interesting for many advanced applications. However, the development of novel ink materials with high intrinsic 3D printing performance has been proven to be a major challenge. Herein, a novel 3D printable organic–inorganic hybrid hydrogel is developed from three components, and characterized in detail in terms of rheological property, swelling behavior and composition. The nanocomposite hydrogel combines a thermoresponsive hydrogel with clay LAPONITE® XLG and in situ polymerized poly( N, N -dimethylacrylamide). Before in situ polymerization, the thermogelling and shear thinning properties of the thermoresponsive hydrogel provides a system well-suited for extrusion-based 3D printing. After chemical curing of the 3D-printed constructs by free radical polymerization, the resulting interpenetrating polymer network hydrogel shows excellent mechanical strength with a high stretchability to a tensile strain at break exceeding 550%. Integrating with the advanced 3D-printing technique, the introduced material could be interesting for a wide range of applications including tissue engineering, drug delivery, soft robotics and additive manufacturing in general.